Asian Woolly Hackberry Aphid, Shivaphis celti Das (Insecta: Hemiptera: Aphididae) - Susan E. Halbert; Paul M. Choate (EDIS, 2005)
An Asian woolly hackberry aphid, Shivaphis celti Das, was found for the first time in Florida in Jacksonville, Duval County, on sugarberry (Celtis laevigata Willd.) on 13 August 1997 by Florida Department of Agriculture & Consumer Services' Division of Plant Industry Plant Inspector Flewellyn W. Podris. Since then, these Asian woolly hackberry aphids have been collected in counties spanning most of Florida. Shivaphis celti was found in Georgia about a year before its discovery in Florida. This document is EENY-288, originally published as DPI Entomology Circular 392, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.